Local Synchronization of Web Applications with Audio Markings - Lemos, Victor S.; Ferreira, Rafael F.; Segundo, Ricardo Mendes Costa; Costalonga, Leandro Lesqueves; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
Synchronization is about providing coherent orchestration of events or resources involved in a multimedia application. In a synchronized application, the user has the notion that his device's content is directly connected with others. In this paper we discuss the existing synchronization techniques, their advantages and disadvantages, and the current implementations and usage. We also present our open source solution for local synchronization of Web applications, the Audio Markings API, detailing its usage, components and functionalities. The focus of this paper is on smart devices such as smartphones, tablets and laptops since they often have built-in microphones and speakers - resources that we intend to explore. In addition to that, those devices are perfectly capable of running full-featured web browsers, something that we also need to take advantage of. Our goal is to give developers an alternative for synchronization of Web applications, using the Web browser as a platform and the sound as a bridge.